A League to Preserve Empires: Understanding the Mandates System and Avenues for Further Scholarly Inquiry. - Wempe, Sean Andrew (American Historical Review, 2019)
A century after the victorious Allied powers distributed their spoils of victory in 1919, the world still lives with the geopolitical consequences of the mandates system established by the League of Nations. The Covenant article authorizing the new imperial dispensation came cloaked in the old civilizationist discourse, entrusting sovereignty over "peoples not yet able to stand by themselves under the strenuous conditions of the modern world" to the "advanced nations" of Belgium, England, France, Japan, and South Africa. In this series of "reflections" on the mandates, ten scholars of Europe, Africa, the Middle East, Asia, and the international order consider the consequences of the new geopolitical order birthed by World War I. How did the reshuffling of imperial power in the immediate postwar period configure long-term struggles over minority rights, decolonization, and the shape of nation-states when the colonial era finally came to a close? How did the alleged beneficiaries—more often the victims—of this "sacred trust" grasp their own fates in a world that simultaneously promised and denied them the possibility of self-determination? From Palestine, to Namibia, to Kurdistan, and beyond, the legacies of the mandatory moment remain pressing questions today.